SD Bioline malaria antigen Pf (HRP-2/pLHD) for assessing efficacy of artemisinin combination therapy against plasmodium falciparum in pediatric patients in the Democratic Republic of the Congo - Kilauzi, Albert L.; Tshikuka Mulumba, Jose G.; Magafu, Mgaywa G. M. D.; Matchaba-Hove, Reginald; Tapera, Roy; Magafu, Naoko S.; Tamfum, Jean J. M. (African Field Epidemiology Network, 2016)
The emergence of Plasmodium falciparum resistance to artemisinin combination therapy (ACT) is a worrying development. It calls for close surveillance to monitor the efficacy of the drugs. The objectives of this study were to determine the performance of SD Bioline malaria AgPf(HRP-2/pLDH) 3 band Rapid Diagnostic Test (RDT) against Giemsa-stained blood smear and evaluate the suitability of this test in assessing the therapeutic efficacy of ACT in pediatric malaria patients in the Democratic Republic of the Congo (DRC). Methods: Five hundred and one patients with malaria symptoms were screened for P. falciparum in Kinshasa, DRC. Of the 166 patients who tested positive for P. falciparum at recruitment (day 0), 103 consented to participate in this study and were followed up and retested for P. falciparum on day 3, day 7, day 14, day 21 and day 28. Results: Sensitivity and specificity of the test were significantly high on day 0 and so were their positive and negative predictive values. Higher proportions of false positive cases were observed on the HRP-2 band irrespective of patient parasite densities during the follow up but these were barely seen on the pLDH band. Some patients turned positive during follow up but pLDH readings remained consistent with blood smear readings. Conclusion: SD Bioline malaria AgPf(HRP-2/pLDH) RDT demonstrated high performance in DRC. Thus, the test can be employed to assess the efficacy of ACT in pediatric malaria patients and prioritize areas that require the deployment of advanced testing like polymerase chain reaction (PCR).